TRANSMISI TEKS JAWA DALAM NASKAH BABAD AWAK SALIRA - Isep Bayu Arisandi; Titin Nurhayati Ma'mun; Undang Ahmad Darsa (Widyaparwa, 2022)
This paper aims to reveal the transmission of the text structure and the form of translation in the text of Babad Awak Salira (later referred to as AS). The issue that will be examined in this paper is the transmission of structures and forms of translation that exist in AS manuscript texts. Old poetry is bound by a system of conventions in building structure. The tembang macapat convention system is found in the form of wawacan texts that developed in Sunda. These findings were analyzed by structural theory of the ancient poetry and translation. The application of this theory can be reveal the transmission of structure in the text. The method of research is the philological method and the translation method. Each data in this study was collected using a literature study for analysis. The results of this study include; (1) transmission of structure from macapat tembang to wawacan form in AS script texts; and (2) the form of translation in the use of diction used in the AS manuscript text. The use of the tembang macapat convention in the AS text is balanced with the practice of "translation" and adaptation of several terms as an effort to adjust and understand from Javanese (source) to Sundanese (target).Tulisan ini bertujuan untuk mengungkap transmisi struktur teks dan bentuk penerjemahan dalam teks naskah Babad Awak Salira (selanjutnya disebut AS). Masalah yang dibahas dalam tulisan ini adalah transmisi struktur dan bentuk terjemahan yang ada dalam teks naskah AS. Puisi lama terikat dengan sistem konvensi dalam membangun struktur. Sistem konvensi tembang macapat ditemukan dalam bentuk teks wawacan yang berkembang di Sunda. Temuan ini, dianalisis dengan menggunakan teori struktur puisi lama dan terjemahan. Penggunaan teori tersebut dapat mengungkap transmisi struktur dalam teks. Metode yang digunakan adalah metode filologi dan metode terjemahan. Setiap data dalam tulisan ini dikumpulkan dengan menggunakan studi pustaka untuk dianalisis. Hasil tulisan ini meliputi; (1) transmisi struktur dari tembang macapat menuju bentuk wawacan dalam teks naskah AS; dan (2) bentuk terjemahan dalam penggunaan diksi yang digunakan dalam teks naskah AS. Penggunaan konvensi tembang macapat dalam teks AS diimbangi dengan praktik “terjemahan” dan adaptasi beberapa istilah sebagai upaya penyesuaian dan pemahaman dari bahasa Jawa (sumber) menuju bahasa Sunda (sasaran).